The Distribution of Hydrothermal Minerals at the Golden Cross Epithermal Au-Ag Deposit, Waihi, New Zealand - S F. Simmons; J L. Mauk; A McOnie (The Australasian Institute of Mining and Metallurgy, 1995)
Three cross sections, 200 m apart, display the distribution of indicator hydrothermal minerals across the Empire zone of the Golden Cross epithermal Au-Ag deposit, Waihi, New Zealand. These minerals are used to interpret the temperature and composition of hydrothermal fluids. The distribution of interstratified illite-montmorillonite and illite indicate that temperatures ranged from 140 to >220¦C, with temperatures above 220¦C predominating. The mineral assemblage of quartz-adularia-chlorite-illite-calcite-pyrite envelops the Empire vein system and stockwork, and reflects formation from an alkali chloride water whereas the mineral assemblage of replacement calcite-interstratified illite û montmorillonite-kaolinite forms a carapace and reflects formation from a CO2-rich steam-heated water. Alkali chloride waters appear responsible for the epithermal Au-Ag mineralisation.